Strategi Komunikasi Pemberdayaan UMKM Produk Lokal Masyarakat Kabupaten Hulu Sungai Utara - Haika, Novia Ulfah; Susanto, Didi; Lihu, Decky C. K. (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to: 1) determine the communication strategy for empowering MSMEs carried out by the Hulu Sungai Utara Regional Government. 2) To determine the pattern of empowering MSMEs by the Hulu Sungai Utara Regional Government. 3) To determine the method of cross-sectoral cooperation in evaluating the empowerment of MSMEs in Hulu Sungai Utara. The type of research used is qualitative, namely in the initial stage the researcher conducts identification, then data collection is carried out in depth, starting from observation to compiling reports. Data collection techniques use observation, interview and documentation methods. The results of the study indicate that 1) The communication strategy for empowering MSMEs carried out by the Hulu Sungai Utara Regional Government is currently not optimal 2) The pattern of empowering MSMEs towards the Hulu Sungai Utara Regional Government is not structured and built so that it does not show progress towards MSMEs 3) The method of cross-sectoral cooperation in evaluating the empowerment of MSMEs in Hulu Sungai Utara has not been built and there is no network that is able to encourage existing MSMEs. It is hoped that this research can provide benefits and an initial picture for improvement and development strategies, coaching and communication towards empowering MSMEs in Hulu Sungai Utara Regency, South Kalimantan Province